AGE FALSIFICATION AND ITS IMPLICATION ON AN INDIVIDUAL’S PRODUCTIVITY IN AN ORGANISATION - A. ACHU, AYUK; EGBE EBAGU, TANGBAN; T. A., OMANG; FRANCIS, UYANG; CLETUS EKOK, OMONO; NSOR O, JOHN (International Journal of Psychosocial Rehabilitation, 2021)
The study investigated the impact of age falsification on an individual’s performance in an organisation. Issues of why the phenomenon continues unabated in Nigeria were discussed and chief among them include: unemployment, poverty and government insensitivity to its citizens as concern prompt and regular payment of their retirement benefits. The study made some recommendations which include: Nigerian government should re-evaluate her policy of employment that excludes energetic young persons who are willing to work, on account of age (you must not be above 30 years); Government should objectively and without delay pay off the entitlement of all retirees as this would hitherto allay the fears of Nigerians from retiring as of when due; and, Government through its relevant agencies should arrest and prosecute the perpetrators and accomplices that aid and abet age forgery.